Design Analysis Application with Framework for Exam Question Evaluation - Pulla Pandika Widodo; Hayatullah Khumaini; Al Malikul Ikhwanda Putra (Brilliance: Research of Artificial Intelligence, 2025)
Evaluation of questions is generally carried out by teachers after giving exams to students. The exam is a benchmark to determine students' ability to absorb the subject matter delivered by the teacher through objective and essay questions, all students are expected to be able to answer and solve these questions properly. Exams can be referred to as part of the evaluation to maintain the quality of the questions so that they remain suitable. Therefore, the teacher evaluates the questions by using item analysis manually to get the results of the value in the form of a feasible question, this method will spend a lot of time to calculate one by one the results of student answers and then recap the results of the answers for one class, besides that the accuracy of the results is also low because there can be miscalculations from the teacher that can make the question eligibility value inappropriate. The purpose of this research is to produce a system in the form of an application that is able to analyze questions so that it can help teachers get question analysis quickly. With the concept of the model, view, controller method in the codeigniter framework, a web-based application is designed. The results of the research are in the form of data per question which contains an analysis of the question of difficulty level, differentiating power and checking function by using framework codeigniter.